A Study of Above-Surface Carbon Storage in the Post-Coal Mining AREA of PT Bukit Asam - Misriani Holifah; Lulu Yuningsih; Delfi Lensari; Jun Harbi (Program Pascasarjana Universitas Sriwijaya, 2023)
Both biotic and abiotic natural resources are the capital of the biosphere that may be exploited to meet human needs and promote human welfare. Global warming is a consequence of increasing environmental degradation. During photosynthesis, trees may collect carbon from the atmosphere, separate carbon from oxygen, and release oxygen back into the atmosphere. This investigation was conducted on post-coal mining reclamation land that PT. Bukit Asam (BA) restored in 2009, 2012, and 2015. This study employs a quantitative approach with a purposive sampling methodology. The utilized sampling intensities were 1%, 2.5%, and 5%. The plot chosen is a 20-by-20-meter rectangle. Carbon storage for the 2009 planting time averaged 40.57 tons per hectare over a total area of 32.89 ha. Carbon storage for the planting year of 2012 with a total area of 5.73 hectares and an average carbon storage of 26.37 tons per hectare. Carbon sequestration in 2015 with a total area of 3.90 hectares and an average carbon storage of 20.86 tons per hectare.